First detection of Leishmania of the subgenus viannia in Alipiopsitta xanthops, endemic bird of South America (Bioscience Journal, 2021)
We report the first molecular detection of Leishmania infection (subgenus Viannia) in the yellow-faced parrot (Alipiopsitta xanthops), at a wildlife rehabilitation center located in the city of Campo Grande, Brazil, an endemic area for leishmaniasis. PCRs targeting kinetoplast DNA (kDNA) and the small subunit of ribosomal RNA of Leishmania spp. were performed, both positive, followed by the sequencing of the amplified region of the SSU rDNA gene, which confirmed the identity of the parasite. This is the first report of success obtained in the use of PCR targeting the IRBP (Interphotoreceptor retinoid-binding protein) gene as an internal control in the molecular diagnosis of pathogens in bird species.